THE PRODUCTION AND PHYSICAL CHARACTERISTICS TEST OF ANALOG RICE MADE FROM CASSAVA FLOUR CONTAINING PROTEIN OF SHRIMP - Miftahul Jannah (The University of Lampung, 2015)
Analog rice is one of the foods which are made from various kinds of flour that can be alternative rice. Thepurpose of this research was to create and test the characteristics of analog rice made from cassava flourenriched with shrimp proteins. Observation parameters on this research are moisture content, uniformity ofgrain, bulk density, water absorption and color test. The design of this study is using cassava flour and flourshrimpwith composition of each treatmentas follow : A (100 : 0), B (95 : 5), C (92.5 : 7.5),D(90 : 10), E (85 : 15).This study showed that analog rice produced water content of 12.53%- 14.01%, coarse grain diameter 0.95%-6.64%,moderate coarse grain 21.02%- 37.78%and fine grain55.58%- 78. 03%, bulk density from 0.57 to 0.73g/cm3 and water absorption 71.33% - 118.67%. Based on the analysis of variance (ANOVA), the treatment ofanalog rice influences on the nature of analog rice which is uniformity coarse andmedium with an effect on theresult of bulk density. The dominant color of the resulted analog rice is brown.Keywords: Fraction analog rice, Shrimp flourprotein, Cassava flour.